Age-dependent changes in GI physiology and microbiota: time to reconsider?. Issue 12 (7th September 2018) - An, Ran; Wilms, Ellen; Masclee, Ad A M; Smidt, Hauke; Zoetendal, Erwin G; Jonkers, Daisy
Abstract : Our life expectancy is increasing, leading to a rise in the ageing population. Ageing is associated with a decline in physiological function and adaptive capacity. Altered GI physiology can affect the amount and types of nutrients digested and absorbed as well as impact the intestinal microbiota. The intestinal microbiota is considered a key player in our health, and a variety of studies have reported that microbiota composition is changing during ageing. Since ageing is associated with a decline in GI function and adaptive capacity, it is crucial to obtain insights into this decline and how this is related to the intestinal microbiota in the elderly. Hence, in this review we focus on age-related changes in GI physiology and function, changes of the intestinal microbiota with ageing and frailty, how these are associated and how intestinal microbiota-targeted interventions may counteract these changes.